2007
DOI: 10.1111/j.1468-1331.2007.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and cognitive performances of vascular cognitive impairment no dementia in Japan: the Osaki–Tajiri Project

Abstract: Prevalence, magnetic resonance imaging (MRI) findings, cognitive function and depression are four major aspects of vascular cognitive impairment no dementia (vascular CIND). We performed a community-based study to examine these using 497 community-residents aged 65 years or older. Vascular CIND was defined as a clinical dementia rating (CDR) 0.5 with cerebrovascular disease. Several neuropsychological tests were performed, including MMSE, Geriatric Depression Scale (GDS), and Trail Making Test (TMT). Cerebrova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 38 publications
(52 reference statements)
0
43
1
Order By: Relevance
“…Ishii et al [34] For CDR=0 group, anterior periventricular WML and a test of executive function/processing speed were significantly correlated.…”
Section: Reference Associationmentioning
confidence: 92%
See 4 more Smart Citations
“…Ishii et al [34] For CDR=0 group, anterior periventricular WML and a test of executive function/processing speed were significantly correlated.…”
Section: Reference Associationmentioning
confidence: 92%
“…For executive function/processing speed, out of six studies, three studies [24,27,34] found a significant association between periventricular WMLs and executive function/ processing speed, while only one study [26] found a significant association between subcortical WMLs and executive function/processing speed. Two studies [25,33] did not find any association.…”
Section: Reference Associationmentioning
confidence: 94%
See 3 more Smart Citations